2008
DOI: 10.1007/s00213-008-1435-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential susceptibility to ethanol and amphetamine sensitization in dopamine D3 receptor-deficient mice

Abstract: These results suggest a necessary role for the D3R in EtOH but not AMPH sensitization, possibly through postreceptor intracellular mechanisms. Results also suggest that different neurochemical mechanisms underlie sensitization to different drugs of abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 68 publications
(89 reference statements)
1
17
0
Order By: Relevance
“…The latter finding agrees with our current results with U99194A. We did not, however, observe increases in D3R binding associated with EtOH sensitization (Harrison and Nobrega 2009), possibly because we did not examine brains during the induction phase but only after sensitization was already expressed. Alternatively, EtOH-sensitized mice may become functionally more responsive to D3R ligands by mechanisms other than increases in D3R density.…”
Section: D3rs In Induction and Expression Of Etoh Sensitizationsupporting
confidence: 92%
See 4 more Smart Citations
“…The latter finding agrees with our current results with U99194A. We did not, however, observe increases in D3R binding associated with EtOH sensitization (Harrison and Nobrega 2009), possibly because we did not examine brains during the induction phase but only after sensitization was already expressed. Alternatively, EtOH-sensitized mice may become functionally more responsive to D3R ligands by mechanisms other than increases in D3R density.…”
Section: D3rs In Induction and Expression Of Etoh Sensitizationsupporting
confidence: 92%
“…Since EtOH sensitization was not associated with changes in D3R mRNA expression or binding (Harrison and Nobrega 2009), a functional up-regulation of D3Rs after chronic EtOH, would imply changes in intracellular mechanisms, downstream from the membrane-bound receptor. Interestingly, Richtand et al (2003) reported that following amphetamine sensitization (an effect not associated with changes in D3R binding), rats were less responsive to the D3R agonists PD128907 and 7-OH-DPAT, suggesting a functional down-regulation of D3Rs (Richtand et al 2003).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations